(untitled) (Actual Problems of Psychology in Educational Institutions, 2021)
The article consistently explores the problem of the development of reflection, its principles, considers various aspects of reflection. Scientific sources, works of famous scientists and psychologists are analyzed, qualitative opinions and conclusions are given. The level of development of reflection in young people, their desire for deep thinking, self-study, approach to the analysis of their actions and the ability to exercise self-knowledge are shown. The results of the study are presented, the main features that characterize the level of development of reflexive thinking in adolescence are highlighted. Conclusions are made on the basis of information from scientific works and own research, which summarize the information about the essence of reflection at this age.